Economics as a fundamental factor in the formation of law - Mirkhonov, Miromon (Riga Graduate School of Law, 2023)
In the modern world, taking into account modern trends and processes that deeply affect social behavior, law, as an institution regulating social behavior, is also changing, but nevertheless, the institute of law is experiencing difficulties with responding to modern trends and processes, to a greater extent, due to the inability of researchers and specialists in the field of law to determine the boundaries to solve the problems of law, as well as to determine the consequences and predict the impact of the implementation of a particular law on the social behavior of individuals. Thus, this study, describing and constructing a model of social response to legal changes by using the principles of microeconomic theory, revealed that the model provided by the interdisciplinary stream "Law and Economics" is relevant for determining and responding to current trends, since the elements of microeconomic theory are able to accurately predict the impact of a particular law on social behavior, thereby arguing that when considering and implementing a particular law, it is necessary to be based on economic principles, since they are able to accurately simulate the influence of the institution of law on all aspects of the behavior of individuals in society.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Jurisprudence; Economics; Research Subject Categories::LAW/JURISPRUDENCE::Financial law